CALCULATION OF PARTICLE SIZE OF TITANIUM DIOXIDE HYDROSOL - L. M. Sliapniova (Nauka i Tehnika, 2014)
One of the problems facing chemists who are involved in obtaining disperse systems with micro- and nanoscale particles of the disperse phase is a size evaluation of the obtained particles. Formation of hydrated sol is one of the stages for obtaining nanopowders while using sol-gel-method. We have obtained titanium dioxide hydrosol while using titanium tetrachloride hydrolysis in the presence of organic solvent with the purpose to get titanium dioxide powder It has been necessary to evaluate size of titanium dioxide hydrosol particles because particle dimensions of disperse hydrosol phase are directly interrelated with the obtained powder dispersiveness.Size calculation of titanium dioxide hydrosol particles of disperse phase has been executed in accordance with the Rayleigh equation and it has been shown that calculation results correspond to experimental data of atomic force microscopy and X-ray crystal analysis of the powder obtained from hydrosol.In order to calculate particle size in the disperse system it is possible to use the Rayleigh equation if the particle size is not more than 1/10 of wave length of impinging light or the Heller equation for the system including particles with diameter less than wave length of the impinging light but which is more than 1/10 of its value. Titaniun dioxide hydrosol has been obtained and an index of the wave ration has been calculated in the Heller equation. The obtained value has testified about high dispersiveness of the system and possibility to use the Rayleigh equation for calculation of the particle size in the disperse phase. Calculation of disperse-phase particle size of titanium dioxide hydrosol has corresponded to experimental data of the atomic force microscopy and X-ray crystal analysis for the powder obtained from the system.